Preservation of the heritage of the University of Pernambuco using Damage Maps and Damage Factor of the Corrected Regions: case study in a building at the Oswaldo Cruz University Hospital - Costa, Lorena Vila Bela; Teixeira, Bruna Correia; Monteiro, Eliana Cristina Barreto; Soares, Willames de Albuquerque (Technical and Scientific Journal Green Cities, 2024)
As the element that protects a building and therefore receives the action of aggressive agents from the environment in which it is located, the facade can develop pathological manifestations that compromise its function. With this premise, this article aimed to detect the deterioration in the facades of one of the blocks of the Oswaldo Cruz University Hospital, belonging to the Hospital Complex of the University of Pernambuco. The analysis was based on the joint use of the Damage Map, as a tool for documenting existing pathological manifestations, and part of the Degradation Measurement Method for calculating the Corrected Regions Damage Factor, which allowed establishing, in a qualitative and quantitative, the most prominent damages and the most affected areas on each facade. It was observed the predominance of mold, mildew and peeling paint and that both graphical representation and calculation instruments facilitate the diagnosis of the state of conservation of a building and decision-making regarding preventive and corrective measures to avoid and resolve anomalies.